MENINGKATKAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) PADA MURID SD - Syarifah Aeni Rahman; Ummu Khaltsum (Almeera Education, 2022)
This research is a classroom action research. The output that will result from this research is the application of alternative learning, which is not monotonous so that it can improve students' mathematics learning outcomes. In addition, learning tools will be produced consisting of a syllabus, lesson plans using cooperative learning with the Numbered Head Together type. The subject of this research is class IV SDN Taeng, Gowa Regency with 17 students, 6 male students and 11 female students in the 2021/2022 academic year. This research was conducted in 2 (two) cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. In the implementation of learning with the application of cooperative learning with the type of numbered head together is an action given by students to improve students' social studies learning outcomes. The procedure of this research is to observe student activities and the implementation of learning in accordance with the scenarios that have been prepared. At the end of the cycle, a test of learning outcomes was carried out and the collection of student responses regarding the learning process. The results of observations, test results, and student responses were analyzed, then reflection was carried out to determine improvement plans and further actions. The instruments used in the study included student activity observation sheets, learning implementation observation sheets, learning outcomes tests, and student response questionnaires.